The medical messiahs : a social history of health quackery in twentieth-century America - Young, James Harvey (Princeton legacy library., 1992)
Review: ""The Medical Messiahs is an example of historical writing at its best-scholarly, perceptive, and exceedingly readable. Despite his objectivity, Young's dry humor shines through and illuminates his entire book.""--John Duffy, Journal of Southern History ""This book is written in tight, graceful prose that reflects thought rather than substitutes for it. Done with a sure feel for the larger political, social, and economic background, it demonstrates that historians who would make socially relevant contributions need only adhere to the best canons of their art.""-Oscar E. Anderson, Jr.,